Principle of Mathematical Induction

Asked by prnc_bnrj | 2nd Jul, 2008, 07:23: PM

Expert Answer:

for n = 1

L.H.S.= 31 = 3

R.H.S. = 2x 1+1 = 3

hence, L.H.S = R.H.S

let the result is true for n = k

that is, 3k = 2k+1

let n = k+1

consider L.H.S.

3k+1 = 3.3k

          3.(2k+1)

         = (2k+3)+4k

          2k+3 = 2(k+1) +1= R.H.S.

hence, the result is true for all n.   

Answered by  | 16th Jul, 2008, 04:10: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.